Molecular Epidemiology and Characteristics of CTX-M-55 Extended-Spectrum β-Lactamase-Producing Escherichia coli From Guangzhou, China - Zeng, Shihan; Luo, Jiajun; Chen, Xiankai; Huang, LiShao; Wu, Aiwu; Zhuo, Chao; Li, Xiaoyan (Frontiers in Microbiology, 2021)
In recent years, the CTX-M-55 ESBL-positive rate has gradually increased in the clinic. To identify the molecular epidemiology and characteristics of blaCTX-M-55-positive isolates, a total of 374 non-repetitive ESBL-producing Escherichia coli strains were collected from patients in two hospitals in Guangzhou, and 89 blaCTX-M-55-positive isolates were selected by CTX-M-1-group PCR amplification and confirmed by DNA sequencing. Whole-genome sequencing was used to analyze the resistance phenotype, plasmid types, phylogenetic relationships and genetic environment of the blaCTX-M-55 gene. Conjugation experiments and PCR were performed to confirm whether the plasmid harboring blaCTX-M-55 gene could be transferred. The results showed that all blaCTX-M-55-positive isolates were resistant to ceftriaxone, and 88.76% and 76.40% were resistant to ceftazidime and cefepime, respectively. The resistance rates to levofloxacin and sulfamethoxazole were 66.29% and 59.55%, respectively. However, the sensitivity rate of Piperacillin/tazobactam, Amoxicillin/clavulanate and amikacin exceeded 90%. All blaCTX-M-55-positive isolates were sensitive to carbapenems. Thirty-two STs were detected in theblaCTX-M-55-positive isolates, among which the detection rate of ST1193 was relatively high (19.10%, 17/89), and other ST types were scattered. It remains to be seen whether ST1193 carrying the blaCTX-M-55 gene can become a popular clone strain in this region in the future. The plasmid types carrying the blaCTX-M-55 gene included IncI1, IncFII, IncFIC, IncFIB, IncHI2, IncI2, and IncX/Y, among which the IncI1 and IncFII plasmids were the main plasmids, accounting for 37.80% and 28.09%, respectively. Among them, eleven strains of the IncI1 plasmid existed in ST1193 strains. The blaCTX-M-55 gene was found on chromosomes of 13 isolates, and seemed to be increasing annually. Up to five distinct types of genetic environments surrounding the blaCTX-M-55 gene were analyzed. The most common structure was type II “ISEcp1-blaCTX-M-55-ORF477”. In conclusion, whether ST1193, which carries blaCTX-M-55 gene, will be an epidemic clone of this region in the future remains to be concerned. The plasmids IncI1 and IncFII, and mobile elements such as ISEcp1 and IS26 may be the main factors leading to the spread and prevalence of CTX-M-55 genotypes.